Cryopreservation and Freeze- Drying Protocols - Wolkers, Willem F (Humana Press, 2015)
Cryopreservation and freeze-drying are widely used for long-term storage of biological materials. Methods to safely store specimens in a stable state for extended periods have widespread applications in medicine and agriculture. Using cryopreservation for cell and tissue banking allows samples to be available at the time of need. Ice-free cryopreservation, referred to as vitrification, is receiving increased attention in biobanking. Whereas cryopre served samples are typically stored in liquid nitrogen, dried specimens can be stored at room temperature, which has clear advantages for banking and transport. Freeze-drying involves a freezing and a drying step and hence requires protectants that protect during both freezing and drying.